SUBTITLING STRATEGIES IN TAKEN MOVIE BASED ON GOTTLIEB'S THEORY - Quwayis At Taqi; Dian Wulandari (Asosiasi Dosen Muda Indonesia, 2024)
The analysis of this research is the subtitling strategies in Taken movie by using Gottlieb’s subtitling strategies theory. The researcher only analyzed in early 30 minutes out of 93 minutes randomly. The problem of this research is what the subtitle strategies used in the Taken movie are. The objective of this research is to find out the subtitling strategies contained in Taken movie using Gottlieb’s theory. This research used a descriptive qualitative method. The researcher found 7 strategies that have a relation with Gottlieb’s theory, namely transfer, paraphrase, condensation, decimation, imitation, resignation, and expansion.